Effectiveness Probiotic of Nitrosomonas sp. and Bacillus sp. in Improving the Water Quality and Growth of Tilapia Larasati (Oreochromis niloticus) - Sya’bana, Izzatin Nashiroh; Amalia, Rosa; Harwanto, Dicky (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2024)
Water quality is the main factor that has a major influence on the growth and survival of Tilapia Larasati (Oreochromis niloticus). Nitrosomonas sp. and Bacillus sp. can optimize water quality through nitrification and denitrification processes and optimize feed utilization. This study aims to determine the effectiveness of using probiotic Nitrosomonas sp. and Bacillus sp. in O. niloticus maintenance media in improving water quality and growth. The method used was CRD with 4 treatments and 3 replications, namely treatment A (without probiotic), B (probiotic 1.0 µL/L), C (probiotic 1.5 µL/L), and D (probiotic 2.0 µL/L). This study used an aquarium measuring 40 x 30 x 40 cm filled with 20 liters of fresh water, and filled with 10 fish weighing 6.97 ± 0.20 g each (density of 1 fish/2 liters). Molasses as feed bacteria and probiotics were given according to the treatment dose. Siphon was accomplished twice a week according to the level of turbidity. Water changes once a week as much as 50 - 60%. The results from the study showed that the use of probiotics had a significant effect (P<0,05) in improving water quality and fish growth. The best result observed from treatment C, with the reduce ammonia and nitrite (0.002 and 1.291 mg/L), highest fish growth, specific growth rate, and survival rates (14.63±0.24 g; 2.48±0.01%/day; and 97±0,06%, respectively), and also lowest feed conversion ratio (1.07±0.02). Based on these results, the best dose for improving water quality and growth of O. niloticus is 1.5 µL/L.Key words: aquaculture, bioflock, organic matter, sludge, waste